Childlessness trends in twentieth-century Europe: Limited link to growing educational attainment - Eva Beaujouan; Zuzanna Brzozowska; Kryštof Zeman (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2015)
Childlessness, a driving force of fertility, has undergone strong variations in 20th-century Europe, and educational attainment has been rising continuously. We analyse how these two factors were related to each other over time. Our study is based on census and largescale survey data from 13 European countries, collected in the Cohort Fertility and Education database. We compare the trends in the share of women childless at age 40+ in the 1916-1965 birth cohorts, by level of education. The results suggest that the changes in the educational composition of the population were only marginally related to the overall variation in childlessness rates. With time, the positive educational gradient in childlessness usually decreased: the differences between women of medium/high education and low educated women diminished. However, the childlessness ratio between highly and medium educated women remained stable in Western and Southern Europe and even slightly increased in the East.
Keywords: 300; childlessness; cohort fertility; education; trends; Eastern and Western Europe